Development of an infant formula certified reference material for the analysis of organic nutrients. (15th November 2019) - Lee, Joonhee; Kim, Byungjoo; Lee, Sun Young; Choi, Jongoh; Kang, Dukjin; Lee, Hwasim; Choi, KiHwan; Lee, Hyeyoung; Sim, Hee-Jung; Baek, Song-Yee; Lee, Honghee; Hyung, Seok-Won; et al.
Highlights: An infant formula CRMs for the analysis of organic nutrients was developed. Organic nutrients were certified by IDMS approaches as higher-order reference methods. Homogeneities and stability of the CRM were evaluated by IDMS approaches. Metrological qualities of the certified values were proved by their small uncertainties. Five proximates were value-assigned by interlaboratory comparison. Abstract: Infant formula certified reference material (CRM, KRISS CRM 108-02-003) were developed for the analysis of organic nutrients. The CRM is a milk-based infant formula powder, packaged at 14 g per unit. Ten thousand units were prepared and stored at −70 °C. For the certification of each nutrient, ten units were analyzed for simultaneous value-assignment and homogeneity test. Analytical methods used were isotope dilution mass spectrometry (IDMS) based on liquid chromatography mass spectrometer (LC/MS) or gas chromatography mass spectrometer (GC/MS) as higher-order reference methods.13 vitamins, 3 fatty acids, and total cholesterol were certified. The between-unit relative standard deviation of measurement results for each nutrient ranged 0.2% to 2.5%, showing very good homogeneity. The expanded relative uncertainties of the certified values ranged from 1% to 8%, indicating that they have higher-order metrological quality. The values of proximates (proteins, lipids, carbohydrates, water, and ash) were assigned through inter-laboratory comparisons.